2019
DOI: 10.5812/sdme.81169
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Motivational Beliefs and Cognitive and Metacognitive Strategies with Academic Achievement of Students of Shiraz University of Medical Sciences

Abstract: Background: Success and academic achievement are among the most important goals of both students and educational systems. Researchers have examined the impact of different factors such as intelligence, personality, attitude, study habits, thinking skills and academic motivation on students' academic performance. Objectives: The purpose of this study was to investigate the relationship of motivational beliefs and cognitive and metacognitive strategies with students' academic achievement. Methods: In this descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…To mention other factors, Ceylan (2016) proposed that according to teachers’ beliefs and opinions in his study, students’ self-confident is an essential factor since this factor is important for motivating them, therefore teachers are supposed to consider raising their students self-confidence to get the best results from them. Gharghani et al (2019) instead found that factors including higher self-efficacy and using various cognitive strategies are helpful for students in motivating them and facilitating their learning of the target language. Unlike the previous findings, Yurtseven et al (2015) considered enjoyable learning atmosphere as the most effective factor in motivating the students.…”
Section: Term Definitionmentioning
confidence: 94%
“…To mention other factors, Ceylan (2016) proposed that according to teachers’ beliefs and opinions in his study, students’ self-confident is an essential factor since this factor is important for motivating them, therefore teachers are supposed to consider raising their students self-confidence to get the best results from them. Gharghani et al (2019) instead found that factors including higher self-efficacy and using various cognitive strategies are helpful for students in motivating them and facilitating their learning of the target language. Unlike the previous findings, Yurtseven et al (2015) considered enjoyable learning atmosphere as the most effective factor in motivating the students.…”
Section: Term Definitionmentioning
confidence: 94%